Assessment of zakÄt: A Case Study of Selected Islamic Banks in Malaysia - Ali, Nor Aini; Suhaili Sarif; Mohd Balwi, Mohd Abd Wahab Fatoni; Kamri, Nor â€˜Azzah (International Journal of Economics, Management and Accounting, 2020)
ZakÄt is an obligatory payment imposed upon all types of business including Islamic banking institutions. This paper examines zakÄt (alms due) assessment practices in Islamic banking institutions in Malaysia. Prior studies have mainly examined the payment trend of zakÄt on businesses and the contributing factors of payment. This study was conducted in two zakÄt paying Islamic banks; a local full-fledged Islamic bank and an Islamic subsidiary of a conventional bank. Primary and secondary data were collected. Interviews were conducted with relevant respondents from both banks to obtain hands-on information about zakÄt assessment in Islamic banking institutions. The results reveal that the banks are committed to paying zakÄt. Assessment of the zakÄt due is jointly handled by the Finance and Shariah Departments. The whole process of zakÄt treatment from policies, assessment, and distribution involve all levels in the bank hierarchical structure. As there is no single mandatory zakÄt treatment regulation or standard, each bank has its own approach that led to variances in balance sheet item recognition and ultimately the amount of zakÄtpayable. While the variances are minor for one bank, they become considerably significant for the entire Islamic banking sector in Malaysia. Apart from enriching the Islamic finance literature especially in Islamic banking zakÄt practices, this study will also provide valuable insight for practitioners and the relevant authorities.